High-throughput screening identification of novel immunomodulatory combinations for the generation of tolerogenic dendritic cells - Jia, Sihan; Kim, Jeremiah; Esser-Kahn, Aaron Palmer; Deak, Peter (Frontiers in Medicine, 2024)
Tolerogenic Dendritic Cells (tolDCs) have an exceptional promise as a potential therapy for autoimmune disease and transplantation rejection. TolDCs are a unique phenotype of antigen presenting cells (APCs) that can influence naïve T cells into antigen specific T regulatory cells (Tregs), which can re-establish tolerance against auto/allo-antigens in the long term. Despite their promise, tolDCs have not found clinical success. Most strategies seek to generate tolDCs ex vivo by differentiating naïve dendritic cells (DCs) with immunosuppressive agents such as dexamethasone. Recently, we discovered combinations of toll-like-receptor (TLR) agonist and immunosuppressant agents generate robust tolDCs that produce active and antigen specific Tregs in a strategy which we call Push/Pull Immunomodulation (PPI). The previously published formulation is a complex mixture of three immunosuppressant agents and two TLR agonists administered at two separate timepoints, limiting its clinical potential. Here, we seek to identify simpler and more potent PPI formulations to generate tolDCs using data from a large-scale screening project. Over 40,000 combinations of pathogen-associated molecular patterns (PAMPs) and immunomodulatory small molecules were screened using a modified murine macrophage line, RAW dual cells, to observe the effect of these combinations on two major immune regulatory transcription factors, NF-κB and IRF. Combinations were further screened for inflammatory cytokine activity using a human monocyte cell line, THP-1. From this data, we identified 355 combinations that showed low or moderate IRF activity, low NF-κB activity, low inflammatory cytokine generation and good viability: all hallmarks of tolerogenic potential. We further screened these 355 combinations using bone marrow derived DCs (BMDCs) and identified 10 combinations that demonstrated high IL-10 (tolerogenic) and low TNF-α (inflammatory) secretion. After further optimizing these combinations, we identified two combinations that generate robust tolDCs from BMDCs ex vivo. We further show that these PPI-tolDCs can also generate antigen specific Tregs. These second-generation PPI formulations have significant potential to generate robust tolDCs and strong antigen specific Tregs.